Legal Education—Some Compliments Due It - Wesley A. Sturges (Washington University Law Quarterly, 1957)
The truth is that the vigor of our professional self-criticism has served as a forceful factor in the development of current professional legal education; it has been one of the most significant factors in furthering the pursuit by the law-teaching profession for truth and realism. This trait or devotion to criticism has served as a continuing vitality for the examination and re-examination of the validity of our contribution to the general cause of education.
Keywords: Legal education